Design and Implementation of IoT-Based Smart Election Using ESP32 and RFID - Irawan, Bambang; Ardiyanto, Anggasta Rukma (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
This research aims to design and implement a smart election system leveraging Internet of Things (IoT) technology through the integration of the RFID RC522 module, ESP32 microcontroller, and the MQTT communication protocol, with the goal of improving the efficiency, transparency, and security of the voting process. The research adopts a prototyping approach consisting of four main stages: requirement analysis, system design, performance evaluation, and refinement leading to final implementation. The system enables voter authentication through e-KTP verification using RFID sensors, which is cross-checked against a centralized database. Voting data are transmitted securely via the MQTT protocol and displayed in real-time through a Node-RED dashboard, allowing for continuous monitoring and rapid vote recapitulation. Experimental results indicate a 100% accuracy rate in UID verification, prevention of duplicate voting, and stable system responsiveness. The platform significantly reduces human intervention and the risk of vote manipulation, supporting the credibility and auditability of election results. In conclusion, the proposed IoT-based smart election prototype offers an efficient, scalable, and user-friendly technological solution suitable for local deployment. Future improvements may include the integration of cryptographic techniques, cloud-based data storage, and biometric authentication to enhance system robustness and security.